Sacred queer stories: Ugandan LGBTQ+ refugee lives and the Bible - Van Klinken, A. S. (Religion in Transforming Africa Ser., 2021)
An invaluable insight into the narrative politics and theologies of LGBTQ+ life-storytelling, a key text for those in African Humanities, Queer Studies, Religious Studies, and Refugee Studies.